2007
DOI: 10.1111/j.1532-5415.2007.01094.x
|View full text |Cite
|
Sign up to set email alerts
|

Binocular Visual‐Field Loss Increases the Risk of Future Falls in Older White Women

Abstract: OBJECTIVES: To examine the relationship between binocular visual field loss and the risk of incident frequent falls in older white women. DESIGN: A multicenter, prospective cohort study. SETTING: Four clinic centers within the United States in Baltimore, Maryland; Minneapolis, Minnesota; Portland, Oregon; and the Monongahela Valley, Pennsylvania. PARTICIPANTS: Four thousand seventy‐one community‐dwelling white women aged 70 and older participating in the Study of Osteoporotic Fractures. MEASUREMENTS: Prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 39 publications
5
85
2
3
Order By: Relevance
“…Mobility is known to be impaired with visual field loss [4] and the risk of falls is increased [3,5,28]. Given that patients with DPN also have greater likelihood of gait compromise [29] the risk of injury from falls may be further amplified by the twin mechanisms of impaired mobility control and reduced peripheral vision sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Mobility is known to be impaired with visual field loss [4] and the risk of falls is increased [3,5,28]. Given that patients with DPN also have greater likelihood of gait compromise [29] the risk of injury from falls may be further amplified by the twin mechanisms of impaired mobility control and reduced peripheral vision sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…A multi-centre, prospective, cohort study confirmed the association between visual field loss and falls. 41 Severe binocular visual field loss was significantly associated with frequent falls when adjusting for age, study site, and cognitive function (OR 1.50, 95% CI 1.11-2.02). The data also showed a trend for increasing odds of two or more falls with greater binocular visual field loss (Po0.001).…”
Section: Glaucoma and Fallsmentioning
confidence: 99%
“…Patients with diabetic retinopathy have been included in various studies of falls and visual loss as part of larger groups with visual impairment; 19,41 however, this important group have not been studied separately.…”
Section: Diabetes Mellitus and Fallsmentioning
confidence: 99%
“…Whereas the effect of vision loss on safety has been investigated much more often in older drivers than in older pedestrians, some data are available. The risk of falling increases with declines in visual acuity (for a review, see Harwood, 2001;Ivers et al, 1998), adaptation to the dark (McMurdo and Gaskell, 1991), the binocular visual field (Coleman et al, 2007;Freeman et al, 2007), and contrast sensitivity (Ivers et al, 1998;Lord et al, 1991). Visual acuity loss has also been shown to cause problems in discriminating vehicles from the rest of the road environment (Oxley et al, 1995), and declines in contrast sensitivity are thought to hinder the perception of fixed or moving objects such as sidewalks or oncoming vehicles (Oxley et al, 1995).…”
Section: Impact Of Sensory Changesmentioning
confidence: 99%